Development of novel soft pneumatic adaptive system using switching mechanism - Aditra, Rakhmat Fitranto (2024)
Considering the challenges posed by climate change, buildings and constructions that can adapt to satisfy the occupants' needs and environmental conditions are becoming more critical. Compared to static buildings, adaptive buildings can achieve better overall energy efficiency while meeting or increasing occupant comfort. Soft pneumatic adaptive systems (SPAS) are a well-known and promising example of adaptive systems for the construction sector based on pressurised flexible chambers as actuators. Compared to electromechanical adaptive systems, SPAS has fewer components and complexity and lower energy required to actuate. SPAS can also flex under external load, which is beneficial for external building components. SPAS has been developed and built from small-scale laboratory prototypes and temporary structures to permanent building components. Despite the variety of SPAS built examples, SPAS have rarely been discussed independently. Most of the review studies only discuss SPAS as part of adaptive systems in buildings. Meanwhile, the most popular SPAS example, switchable fritted foil cushions, have an apparent difference from the rest of the SPAS. Some definitions of SPAS in some research cannot include the characteristic of switchable fritted foil cushions. This emphasises the lack of research in this field and the gaps in the state-of-the-art development of SPAS. Thus, this thesis developed and investigated Pneufin, an external shading that employs switching mechanisms used by switchable fritted foil cushions. Based on the literature review, switching mechanisms can lower the actuation pressure of SPAS. With lower actuation pressure, SPAS will only require higher pneumatic pressure when the external load increases. Importantly, this could lead to significant benefits such as lowering the operation energy and reducing the leakage of SPAS, thereby enhancing its overall efficiency. Experiments and simulations were conducted to evaluate the structural performance of Pneufin and its impact on building performance. The experiment and computer models for the structural analysis were based on moment equilibrium rigid static, with specific metric such as angular stiffness. Meanwhile, EnergyPlus was utilised to calculate the building energy and daylighting. Additionally, an analytical method based on isothermal ideal gas equilibrium and leakage experiments were employed to model the required energy to control the Pneufin. The actuation pressure result confirmed the main assumption of this research: Pneufin can be actuated under 1 kPa of pressure or vacuum. However, the pressure or vacuum to resist the external load still depends on the design, construction, and external load itself. The structural analysis revealed a significant non-linear effect of the membrane and its connection to the actuated parts of Pneufin. This non-linear effect imposes limitations on the structural performance of Pneufin. The building performance and inflation energy analysis revealed a promising potential of Pneufin in providing thermal and daylight comfort while significantly reducing building consumption. The effectiveness of Pneufin also correlates with its adaptivity and its control parameters, offering a hopeful prospect for energy-efficient building design. Inflation energy was mostly affected by the leakage and by type of the pumps used which were also correlated with the stiffness required by Pneufin, which confirms the interdependency of SPAS. The results of the structural and building performance analysis suggested further improvements for Pneufin. Fabrication methods, technical aspects, and a comprehensive set of design guidelines for Pneufin development were proposed based on the experience during conducting this research. A basic design tool for Pneufin was also developed based on the most crucial design parameters of Pneufin found during this research. This research has uncovered various types of soft pneumatic adaptive systems that can be further researched in different building contexts and purposes. The new knowledge obtained through the analysis of Pneufin can be instrumental in the development of Pneufin and other similar soft pneumatic adaptive systems. This research also contributes to the diversification of adaptive façades to save building energy while maintaining the building thermal and daylighting comfort.